THE EFFECTIVENESS OF INSTAGRAM AND WEBSITE NEW MEDIA IN THE PRACTICE OF CYBER PUBLIC RELATIONS AT HIGHER EDUCATION INSTITUTION IN INDONESIA - Febrianti, Dwi Anisa; Kriyantono, Rachmat; Sujoko, Anang (UIN Mataram dan Asosiasi Sosiologi Agama Indonesia (ASAGI), 2023)
The internet as a new media has changed the practice of Public Relations by utilizing new media communication technology which has become known as Cyber Public Relations. Cyber Public Relations practices at a public university in Malang utilize new media Instagram, and website as official communication channels. This research aims to identify the effectiveness of using new media as a two-way communication medium with the framework of Dialogic Communication theory. This research is a type of quantitative descriptive research with quantitative content analysis data collection techniques on Instagram features and uploads and the university’s website from 1 June - 31 August 2023. The results of the research indicate that the application of Dialogic Communication principles in managing content and features on the website is effective, with effectiveness of 66.8%. Meanwhile, the application of Dialogic Communication principles in content management on Instagram is less effective, with an effectiveness of 48%. Researchers suggest that to achieve two-way communication between universities and the public, as well as effective implementation of the Dialogic Loop principle, the Public Relations Division of the university needs to manage content that can facilitate direct dialogue between the institution and the public, for example via the comment column, or conversation space on Instagram or the website.